In vitro Antioxidant and Anticancer Activity of Ethanolic Extract of Defatted Rice Bran on MCF-7 (Breast) and A549 (Lung) Cancer Cell Lines - Avanthi, P; Vigasini, Nora (Asian Journal of Biological and Life Sciences)
Rice bran, a by-product of milling industries is a nutrient dense material basically used as animal feed. Phytochemicals present in rice bran have potent bioactive compounds that can be used to prevent various non-communicable diseases such as cancer. The widespread prevalence of cancer impels research to look for substances that are anti-cancerous in nature. This study involved the in-vitro assessment of antioxidant and anticancer activity of ethanolic extract of defatted rice bran (DFRB). Rice bran was stabilized, defatted and an ethanolic extract was prepared. Phytochemical analysis, total polyphenol content (TPC) and total flavonoid content (TFC) of DFRB was done. Antioxidant activity was measured using 1,1-diphenyl-2-picrylhydrazyl (DPPH) assay and hydrogen peroxide scavenging assay. Cytotoxicity was assessed using MTT assay on breast (MCF-7) and lung (A549) cancer cell lines. Phytochemical screening showed the presence of terpenoids, cardiac glycoside, flavonoids, alkaloids, quinone and phenols. The TPC and TFC was 1.15± 0.34 mg GAE/g and 4.69± 0.40 mg RE/g respectively. DFRB extract showed significant antioxidant activity that was dose dependant, with an IC50 value of 7.82 and 111.68 μg/mL for DPPH and hydrogen peroxide scavenging assays respectively. The viability of MCF-7 and A549 cells decreased with the addition of DFRB extract with IC50 values of 174 and 145 μg/mL respectively. This study reveals the potential of DFRB extract as an antioxidant and anticancer agent, however a thorough investigation of the underlying mechanisms is required for DFRB to be considered as a therapeutic agent by pharmaceutical industries.
Keywords: Anticancer; Antioxidant; Defatted Rice Bran; Ethanolic Extract; Stabilized